Enzymatic synthesis using glycoside phosphorylases. (11th February 2015) - O'Neill, Ellis C.; Field, Robert A.
Graphical abstract: Highlights: An extensive survey of the currently known carbohydrate phosphorylases is presented. The utility of phosphorylases in glycoside synthesis is discussed. Future directions for the discovery and development of phosphorylases for use in synthesis are proposed. Abstract: Carbohydrate phosphorylases are readily accessible but under-explored catalysts for glycoside synthesis. Their use of accessible and relatively stable sugar phosphates as donor substrates underlies their potential. A wide range of these enzymes has been reported of late, displaying a range of preferences for sugar donors, acceptors and glycosidic linkages. This has allowed this class of enzymes to be used in the synthesis of diverse carbohydrate structures, including at the industrial scale. As more phosphorylase enzymes are discovered, access to further difficult to synthesise glycosides will be enabled. Herein we review reported phosphorylase enzymes and the glycoside products that they have been used to synthesise.